Informal university technology transfer: a comparison between the United States and Germany - Christoph Grimpe; Heide Fier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Existing literature has confined university technology transfer almost exclusively to formal mechanisms, like patents, licenses or royalty agreements. Relatively little is known about informal technology transfer that is based upon interactions between university scientists and industry personnel. Moreover, most studies are limited to the United States, where the Bay-Dole-Act has shaped the institutional environment since 1980. In this paper, we provide a comparative study between the United States and Germany where the equivalent of the Bay-Dole-Act has come into force only in 2002. Based on a sample of more than 800 university scientists, our results show similar relationships for the United States and Germany. Faculty quality which is however based on patent applications rather than publications serves as a major predictor for informal technology transfer activities. Hence, unless universities change their incentives (e.g., patenting as one criterion for promotion and tenure) knowledge will continue to flow out the backdoor.
Keywords: J61; O33; 330; informal university technology transfer; cross-country comparison; Forschungskooperation; Wissenschaftler; Wissenstransfer; Technologietransfer; Vergleich; Deutschland; USA